Pengaruh Kepercayaan dan Persepsi Nilai terhadap Kepuasan Konsumen - suryani, wan; Amelia, Wan Rizca; Ginting, Maretta (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
Many factors can affect consumer satisfaction and in this study analyzed how the influence of trust and perception of value on consumer satisfaction Goods Cafe in Medan Selayang District. This type of research is associative with quantitatif approach. The population in this study were consumers who visited Goods Cafe in Medan Selayang District for a month with an average of 195 consumers. The research sample was taken by accidental sampling and the determination of the number using the Slovin formula obtained 66 samples. Data collection techniques through questionnaires and documentation. The analysis technique used multiple linear regression analysis and classical assumption tests were also carried out. The results of the study showed that partially trust and perception of value had a positive and significant effect on consumer satisfaction. Simultaneously, both variables of trust and perception of value had a positive and significant effect on consumer satisfaction Goods Cafe in Medan Selayang District. It is recommended that Goods Cafe management try to increase consumer trust, for example by increasing the number of officers/waiters especially on Sundays/holidays and also trying to improve service so that consumers have a good perception of Goods Cafe as the best choice of place to visit.